PENATALAKSANAAN OKUPASI TERAPI PADA DOWN SYNDROME MENGGUNAKAN BEHAVIOR MODIFICATION DAN SENSORI INTEGRASI DALAM AKTIVITAS TOILETING (CASE STUDY) - KAMESWARI, Eka TALIA; Arsyi, Reza Nur; Luthfi, Muhammad; Gidion, Hermito; Kosasi, Ayleen Alicia; Aziz, Abdul; Mohd, Erna Faryza (Jurnal Vokasi Indonesia, 2024)
Down syndrome is a condition of physical and mental developmental delays caused by chromosomal abnormalities. Children with Down syndrome generally show differences in motor development compared to other children, including delays in developing independence in daily activities. This study evaluates An. N, a 9-year and 9-month-old child with Down syndrome, who has issues with independence, particularly in toileting activities. To address this issue, an occupational therapy program was implemented using behavior modification and sensory integration approaches. The behavior modification techniques employed included positive reinforcement and prompting (physical, verbal, gestural, modeling), while the sensory integration techniques involved play. The results of the study showed that after 20 therapy sessions, An. N's ability in toileting activities significantly improved, as reflected by the change in the WeeFIM assessment score for the toileting component from 1 (Total assistance) to 5 (Supervision). This indicates an improvement in the child's independence in daily activities.